2022
DOI: 10.1021/jacs.2c08475
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Selenol-ene Using Rh-Hydride Catalysis

Abstract: This study showcases the first enantioselective hydroselenation of styrenes. Organoselenium building blocks are accessed with selectivity for the branched isomer. Through a Rh-hydride pathway, C−Se bonds can be forged with excellent regioand enantiocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In our previous hydrofunctionalization studies, the choice of counterion associated with the Rh center played an important role in the reactivity. [12] On this basis, we evaluated various neutral and cationic rhodium catalysts (entries 2-4). We found Rh(cod) 2 BF 4 catalyzed the hydroheteroarylation to generate the desired alkylated indole 3aa in 93% isolated yield with great selectivity (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous hydrofunctionalization studies, the choice of counterion associated with the Rh center played an important role in the reactivity. [12] On this basis, we evaluated various neutral and cationic rhodium catalysts (entries 2-4). We found Rh(cod) 2 BF 4 catalyzed the hydroheteroarylation to generate the desired alkylated indole 3aa in 93% isolated yield with great selectivity (entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…To our delight, we found that the desired alkylated indole 3 aa bearing all‐carbon quaternary center at the C3‐position was obtained in 68 % yield by using [Rh(cod)Cl] 2 and thiophenol as co‐catalysts (entry 1). In our previous hydrofunctionalization studies, the choice of counterion associated with the Rh center played an important role in the reactivity [12] . On this basis, we evaluated various neutral and cationic rhodium catalysts (entries 2–4).…”
Section: Resultsmentioning
confidence: 99%
“…insertion, 8 and ylide formation/rearrangement reactions. 9 It is also used frequently for the synthesis of sulfides and selenides via the construction of C(sp 3 )–S/Se bonds, including S–H/Se–H insertion, 10 [2,3]-rearrangement (Doyle–Kirmse rearrangement 11 and Sommelet–Hauser rearrangement), 12 and [1,2]-rearrangement (Stevens rearrangement). 13 However, the method for the construction of C(sp 2 )–S/Se bonds is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…Any attempt to extend this reaction to vinylarenes would meet with failure because such a process would require a diene moiety for the key hydrogen transfer. In 2022, Dong and Yang reported a Rh–H-catalyzed hydroselenation reaction, and that work represents a precious example of hydrofunctionalization of styrene using chalcogen nucleophile . Nevertheless, the transition-metal-catalyzed asymmetric hydrosulfonylation of vinylarenes remains an unsolved challenge.…”
Section: Introductionmentioning
confidence: 99%